Avaliação da vulnerabilidade e perigo à contaminação do Aquifero Utiariti usando o método SI - Duarte, Rejane Suellen da Silva (2016)
The groundwater is the primary source of drinking water in the Sinop-MT municipality. The Utiariti is the main aquifer in this region and it is characterized as a porous reservoir of fresh water. Due to its high hydraulic conductivity and shallow water level, it is susceptible to the contamination. In addition, the poor septic system, where the domestic sewage is threw to the unappropriated septic tanks, is one of the major factors of the groundwater pollution in this area. In this context, the main aim of this study was to evaluate the vulnerability of Utiariti Aquifer to the contamination in the Sinop municipality using the SI methodology (Susceptibility Index). The SI results showed that the contamination vulnerability is moderate to high. The moderate class of vulnerability occurs in 70% of area, and it indicates that the continuous dumping of contaminates can reach the saturated aquifer zone. For determinate this vulnerability index, the water depth (D) and the land uses (LU) was used as important parameters. The high level of susceptibility takes place in 30% of the area. Although the unsaturated zone can absolve or transform part of these contaminants, the pollution exposure is intense in this area. Therefore, it is recommended strategies to prevent and protect the Utiariti Aquifer by the monitoring of water quality and orientation for an appropriated land uses.